PERBEDAAN LABA USAHA UNIT DAN NON PERFORMING LOAN DI BRI UNIT PORONG SEBELUM DAN SESUDAH BENCANA LUMPUR LAPINDO - Istanti, Lulu Nurul (Fakultas Ekonomi, UIN Maliki Malang, 2008)
The aims of this study are to analyze the performance of the Bank Rakyat Indonesia Unit Porong before and after the lapindo hot mudflow disaster. The result of the study could be useful for those who are concerned with the profitability and liquidity of the bank.The study involved Bank Rakyat Indonesia Unit Porong using purposive sample sampling method. The researcher also collected the monthly financial report of the sampling from February 2005 trough Augustus 2007A number of statistical roles were used for data analysis including the data normality test and paired sample t-test. Result indicated that all variables are normally distributed. The paired sample t-test suggested that while significant difference exists in the Laba Usaha Unit between the two periods. There was no significant difference in the Non Performing Loans between the two periods.